Performance of photovoltaic generators under superficial dust deposition on their modules derived from anthropogenic activities - Comerio, Alessandra; Scarpart, Thiago Tassinari; Krause, Rafael Cabral Knaip; Fernandes, Mariana Rampinelli; Muniz, Pablo Rodrigues (Acta Scientiarum. Technology, 2020)
Performance of photovoltaic generators is affected by, among other factors, surface dust deposition on photovoltaic modules, which causes uniform soft shading, reducing the solar radiation reaching photovoltaic cells. Several researches have demonstrated this effect through studies in specific localities. As deposition of particulate matter varies according to locality, these results cannot be generalized or used in other places, since these studies do not characterize their local dust. Considering these research opportunities, this paper evaluates the deposition effects on photovoltaic modules by different types of dust from anthropogenic activities recurrent in urban areas, a typical situation of distributed microgeneration. Particulate matter of iron ore, building construction, quarry, and mineral coal are characterized morphologically and dimensionally. Then, their effects on photovoltaic module performance are analyzed under different deposition densities according to typical urban deposition rates. The results show that the different dust materials studied attenuate the power generation capacity to different extents, and superficial dust density of the particulate matter also produces different effects. These results can be used in performance and economic feasibility analyzes of photovoltaic generators in different locations with similar pollution characteristics.